A legacy for the future. - Severin, Howie G.; Saturay, Ariel; Yap, April T.; Paz, Cynthia C.; Lim, Stanley; Papag, Ron M. (AV029, 1997)
Features the state of Philippine biodiversity and people's initiatives to protect the environment. Highlights the Banahaw, Palapag and Malindang experiences.